Livre de Fumar: Grupo de Cessação do Tabagismo: Relato de Experiência - Borges, Larissa Barbosa Martins (2024)
This paper aims to report the experience of accompanying a smoking cessation group, as well as the achievements and challenges experienced along the journey of quitting tobacco. Held at the Amélio Marques Outpatient Clinic of the Hospital de Clínicas of the Federal University of Uberlândia, the Nursing course extension project led by a coordinating teacher together with a multidisciplinary team, works on a voluntary basis using the cognitive-behavioral approach and guidelines of the National Program of Tobacco Control. The group has four face-to-face sessions and two virtual sessions, where manuals from the “Quitting Smoking Without Mysteries” programs are used. The group started with 11 participants and 4 completed all the sessions: one stopped smoking completely, two no longer smoke and are still on drug therapy, and one significantly reduced the amount. Factors such as nicotine dependence and anxiety have an impact on. An welcoming, non-judgmental environment and mutual support were fundamental. More resources and visibility can contribute to better results, emphasizing group support on the path towards a smoking free life